KAJIAN BIBLIKA TERHADAP BERITA HOAX TEMPO DULU TERHADAP BAHAYA BERITA HOAX DALAM MEDIA SOSIAL MASA KINI - Johanes Witoro (STT BIBLIKA JAKARTA, 2020)
This research is intended to find a biblical study between past hoax news and the dangers of hoax news in today's social media. This study uses a qualitative writing method by using exsegesa study of the Bible as the basis of essential truth, supported by various sources related to the existing discussion topics. In the discussion, it turns out that there is a similarity between